impact of storytelling training on managerial applications of storytelling in South African organisations - Shih, Feng-Ju (Ray) (My University, 2012)
The purpose of this research is to explore the different practical managerial applications of stories and storytelling used by managers in South African organisations after they have received formal storytelling training. This study was consequently an accumulation of views on the different managerial applications of storytelling in the context of South African organisations after partaking in formal training on storytelling. Nine senior business managers and the lecturer of the Storytelling Elective for the Wits Business School were interviewed; all ten interviews were recorded and summarised. The results have been recorded in bullet form, and summarised with key findings, patterns and trends. These findings have been supported with selected direct quotes and electronic documents from the interviewees. From the review of literature and interviews with ten interviewees, the following emerged:  All the identified application themes explored by the various literatures namely, 1. Corporate culture and identity (a. Communicating vision and mission; b. Transmitting norms, c. Values and ideals; d. Genesis narrative and organisational history; e. Brand enhancement; f. Socialization of organisation members); 2. Knowledge management (a. Meaning making and sense making; b. Training and teaching; c. Learning; Problem solving and decision making; d. Innovation and new product development) and 3. Change management seemed to be supported to a greater or lesser extent by the result of the interviews.  An additional application was identified from the conducted interviews where stories were used to enhance engagement and sharing in a professional working environment. This was not specifically identified under the literature review.  It appears that the definition and possible applications of storytelling remain unclear to some respondents, even after receiving formal training. In most instances, the applications are applied in a less deliberate style rather than implementing stories in a conscious and methodical manner by managers who have undergone formal storytelling training. The results indicate that managers utilise the various applications of storytelling to some extent; however it appears that the majority cannot see the broader possibilities of its uses in their respective professional areas. As a result, areas of possible further research were identified.
MBA thesis - WBS
Keywords: Storytelling; Story telling